2023
DOI: 10.1111/jcmm.17943
|View full text |Cite
|
Sign up to set email alerts
|

Glucose dysregulation promotes oncogenesis in human bladder cancer by regulating autophagy and YAP1/TAZ expression

Shi Li,
Banzhan Ruan,
Zhi Wang
et al.

Abstract: Glucose dysregulation is strongly correlated with cancer development, and cancer is prevalent in patients with Type 2 diabetes (T2D). We aimed to elucidate the mechanism underlying autophagy in response to glucose dysregulation in human bladder cancer (BC). 220 BC patients were included in this retrospective study. The expression of YAP1, TAZ and AMPK, EMT‐associated markers, and autophagy marker proteins was analysed by immunohistochemistry, western blotting, and quantitative real‐time PCR (qPCR). Further, T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…31,32 Therefore, YAP1/TAZ has been a promising target for preventing abnormal remodelling in numerous diseases. [33][34][35] Guérin A et al once have reported that limb expression 1 (LIX1) downregulation alters mitochondrial quality control pathway to control the fate of digestive mesenchyme-derived cells by regulating YAP1 and TAZ activity. 36 Here, we presented that YAP1 and TAZ can bind to mTORC1 to activate or inhibit the target genes in mitochondrial quality control pathway.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Therefore, YAP1/TAZ has been a promising target for preventing abnormal remodelling in numerous diseases. [33][34][35] Guérin A et al once have reported that limb expression 1 (LIX1) downregulation alters mitochondrial quality control pathway to control the fate of digestive mesenchyme-derived cells by regulating YAP1 and TAZ activity. 36 Here, we presented that YAP1 and TAZ can bind to mTORC1 to activate or inhibit the target genes in mitochondrial quality control pathway.…”
Section: Discussionmentioning
confidence: 99%